2015
DOI: 10.1002/2014jf003311
|View full text |Cite
|
Sign up to set email alerts
|

Do intertidal flats ever reach equilibrium?

Abstract: Various studies have identified a strong relation between the hydrodynamic forces and the equilibrium profile for intertidal flats. A thorough understanding of the interplay between the hydrodynamic forces and the morphology, however, concerns more than the equilibrium state alone. We study the basic processes and feedback mechanisms underlying the long-term behavior of the intertidal system, restricting ourselves to unvegetated intertidal flats that are controlled by cross-shore tidal currents and wind waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 57 publications
4
52
0
Order By: Relevance
“…By contrast, a recent study of Maan et al (2015) introduced the possibility of a perpetual imbalance of the tidal flat's Fig. 12 Residual fluxes of silt in the shallow subtidal region for a nowaves case with flood-dominant boundary tide.…”
Section: Residual Transport and Balancing Mechanismsmentioning
confidence: 99%
“…By contrast, a recent study of Maan et al (2015) introduced the possibility of a perpetual imbalance of the tidal flat's Fig. 12 Residual fluxes of silt in the shallow subtidal region for a nowaves case with flood-dominant boundary tide.…”
Section: Residual Transport and Balancing Mechanismsmentioning
confidence: 99%
“…By including a morphodynamic feedback, Pritchard et al (2002) and Pritchard and Hogg (2003) confirmed the (tide forced only) equilibrium profiles by Friedrichs and Aubrey (1996). More recently, Maan et al (2015) suggested the possibility that mudflats under crossshore tidal forcing, either prograde or retreat while maintaining a migrating, several kilometres long, equilibrium profile shape. Zhou et al (2015aZhou et al ( , 2016 explored the impact of grain sorting and consolidation on mudflat morphodynamics, while Marani et al (2007), Mariotti and Fagherazzi (2010) and Zhou et al (2015b) provide examples on the impact of vegetation and its feedback on morphodynamics.…”
Section: Introduction Frameworkmentioning
confidence: 97%
“…However, at the top of the tidal flat, the tidal current velocities fall considerably (Maan et al, 2015;Van Straaten & Kuenen, 1958), see also Figure 2. However, at the top of the tidal flat, the tidal current velocities fall considerably (Maan et al, 2015;Van Straaten & Kuenen, 1958), see also Figure 2.…”
Section: Tides Onlymentioning
confidence: 94%
“…These studies indicate relationships between the SSC in the deeper waters (where longitudinal currents dominate) and the transverse profile slope and progradation velocity of the flats (Friedrichs, 2011;Liu et al, 2011;Pritchard & Hogg, 2003; see Figure 1 for an orientation on the considered domain). In this contribution we use the basis of the "Lagrangian equilibrium state" (Maan et al, 2015) to derive quantitative relationships between the progradation speed, the SSC in the adjacent waters, wave-induced erosion, and SLR. In this contribution we use the basis of the "Lagrangian equilibrium state" (Maan et al, 2015) to derive quantitative relationships between the progradation speed, the SSC in the adjacent waters, wave-induced erosion, and SLR.…”
Section: H(t)u(t)c(t)dtmentioning
confidence: 99%
See 1 more Smart Citation